(2S)-2-(3-(1-Carboxy-5-(4-(211)At-Astatobenzamido)Pentyl)Ureido)-Pentanedioic Acid for PSMA-Targeted α-Particle Radiopharmaceutical Therapy - Kiess, Ana P. (J Nucl Med, 2016)
Alpha-particle emitters have a high linear energy transfer and short range, offering the potential for treating micrometastases while sparing normal tissues. We developed a urea-based, (211)At-labeled small molecule targeting prostate-specific membrane antigen (PSMA) for the treatment of micrometastases due to prostate cancer (PC). Methods: PSMA-targeted (2S)-2-(3-(1-carboxy-5-(4-(211)At-astatobenzamido)pentyl)ureido)-pentanedioic acid ((211)At-6) was synthesized. Cellular uptake and clonogenic survival were tested in PSMA-positive (PSMA+) PC3 PIP and PSMA-negative (PSMA−) PC3 flu human PC cells after (211)At-6 treatment. The antitumor efficacy of (211)At-6 was evaluated in mice bearing PSMA+ PC3 PIP and PSMA– PC3 flu flank xenografts at a 740-kBq dose and in mice bearing PSMA+, luciferase-expressing PC3-ML micrometastases. Biodistribution was determined in mice bearing PSMA+ PC3 PIP and PSMA– PC3 flu flank xenografts. Suborgan distribution was evaluated using α-camera images, and microscale dosimetry was modeled. Long-term toxicity was assessed in mice for 12 mo. Results: (211)At-6 treatment resulted in PSMA-specific cellular uptake and decreased clonogenic survival in PSMA+ PC3 PIP cells and caused significant tumor growth delay in PSMA+ PC3 PIP flank tumors. Significantly improved survival was achieved in the newly developed PSMA+ micrometastatic PC model. Biodistribution showed uptake of (211)At-6 in PSMA+ PC3 PIP tumors and in kidneys. Microscale kidney dosimetry based on α-camera images and a nephron model revealed hot spots in the proximal renal tubules. Long-term toxicity studies confirmed that the dose-limiting toxicity was late radiation nephropathy. Conclusion: PSMA-targeted (211)At-6 α-particle radiotherapy yielded significantly improved survival in mice bearing PC micrometastases after systemic administration. (211)At-6 also showed uptake in renal proximal tubules resulting in late nephrotoxicity, highlighting the importance of long-term toxicity studies and microscale dosimetry.